Corrosion behaviour of 2A97-T6 Al-Cu-Li alloy: The influence of non-uniform precipitation. (March 2018) - Zhang, Xinxin; Zhou, Xiaorong; Hashimoto, Teruo; Liu, Bing; Luo, Chen; Sun, Zhihua; Tang, Zhihui; Lu, Feng; Ma, Yanlong
Highlights: The distribution of T1 phase precipitates in the Al-Cu-Li alloy is non-uniform. Dense T1 phase precipitate bands and precipitate-free bands exist within selected grains. Corrosion occurs preferentially at the dense T1 phase precipitate bands. The selective dissolution of T1 phase results in intragranular corrosion. Abstract: In the present study, the influence of precipitate distribution on the corrosion behaviour of 2A97-T6 Al-Cu-Li alloy in 3.5 wt.% NaCl solution is investigated. It is found that localized plastic strain introduced to the alloy during sheet fabrication leads to the formation of dense T1 (Al2 CuLi) phase precipitate bands and precipitate-free bands within selected grains during aging. Preferential dissolution of T1 phase in the dense precipitate bands results in intragranular corrosion in the alloy, in the form of corrosion bands. Further, the dissolution of the alloy matrix propagates in the form of crystallographic corrosion pit.